An Experimental Study to Analyze the Black Cotton Soil Strength by Combining GGBS and Rice Husk Ash Powder Using CBR Test (International Journal of Innovative Research in Engineering & Management, 2023)
The technological advancement ensures  the durability of the constructed roads in a cost friendly  manner. The utilisation of soil additives, such as lime,  cement, cement kiln dust, Ground Granulated Blast  Furnace Slag (GGBS) Powder, Rice husk ash (RHA),  limestone ash and asphalt, has become a prevalent  technique for enhancing the geotechnical characteristics  of substandard building materials, particularly expansive  soils. The present study aims to examine the impact of  (GGBS) Powder and rice husk ash on the engineering  characteristics of black cotton soil (BCS). In this work,  the strength of BCS has been examined by incorporating  different concentration of GGBS and rice husk ash power  for both soaked and unsoaked soil samples using  California Bearing Ratio (CBR) test. The findings of the  study suggested that the optimal combination of materials  for achieving the highest soaked CBR value is a  proportion of 10% Rice husk ash powder and 8% GGBS  Powder when added to soil. Therefore, this ratio can be  utilized in the construction of road pavements and  embankments.
Keywords: CBR test; Ground granulated blast furnace Slag; Rice husk ash; Road pavement; Expansive soil; Black cotton Soil strength